Academic Tutoring and Academic Performance: An Analysis at UNSM - Reátegui , M.SP. Augusto Ricardo Llontop; Rosado, Dra. Carmela Elisa Salvador; Monja, Víctor Manuel Vallejos (Journal of Ecohumanism, 2024)
This study explores the relationship between the comprehensive tutoring system and the academic performance of students at the National University of San Martín (UNSM). The study addresses the issues faced by the institution, whose tutoring programme lacks a coordinated approach between faculties, a strong clinical psychology team, and teachers with adequate tutoring skills, resulting in a loss of student interest. The aim was to determine whether there is a significant relationship between the comprehensive tutoring system and academic performance. A quantitative methodology with a non-experimental, cross-sectional design was used. A questionnaire was applied to 342 students selected through stratified probabilistic sampling, and their academic performance was analysed. The results indicated that, although most students perceived the tutoring system as acceptable, no significant correlation with their academic performance was found. In conclusion, the current tutoring system does not appear to directly influence academic performance, suggesting a need to review its structure and integration. This study addresses a gap in the literature by examining the relationship between tutoring and academic performance in Peruvian universities, aligning with SDG 4 (Quality Education). Future studies should investigate contextual and personal factors that may influence academic performance.